Pengaruh variasi konsentrasi terhadap sifat listrik lapisan tipis CoFe2O4 - Hendra Anwar; Jepri Limbong; Hary Sanjaya (Pelantar Press, 2022)
A thin layer is a very thin layer of material (organic, inorganic metal or a mixture of organic metals) which has the properties of a conductor, a semiconductor, a superconductor or an insulator. CoFe2O4 nanoparticles are very popular materials to be developed in the field of electricity and magnetism because they have cubic magnetocrystalline properties and high coercivity properties, as well as medium saturation magnetization. Sol-gel is one of the techniques in the manufacture of thin films that involves chemical processes in the form of hydrolysis and condensation reactions. Sol-gel dip coating is a technique for making a thin layer that has several advantages, namely a simple method, easy, few precursors so that it saves production costs and does not damage the environment. XRD test results of a 0.20 M CoFe2O4 thin layer found a peak in the 2Ө 18.1152 region with a diffraction pattern (111). The highest UV-Vis absorbance peak at a wavelength of 285 nm was 2.5423 A and the lowest bandgap value was 2.79 eV. The resistance value is 6.46 and the resistivity value is 0.00016225 m.